2013
DOI: 10.1149/2.012311eel
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Activity of Nanoroughened GaN by Dry Etching

Abstract: The influence of nanostructuring on the photoelectrochemical (PEC) properties of GaN is investigated. GaN nanopillar arrays are fabricated by inductively-coupled-plasma dry etching of a GaN epitaxial layer, using a self-assembled Ni cluster mask. Pillars of 0.4-1.6 μm in height were prepared and were investigated photoelectrochemically. After nanoroughening, the surface area increases up to 6 times and the plateau photocurrent increases by 84% with respect to planar GaN. The pillar structure provides abundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…12 Although n-type GaN has a high absorption coefficient (10 5 cm -1 ) for supra bandgap light 13 and superior minority carrier diffusion length (200-300 nm), 14 recent studies have shown that the photoactivity of n-GaN can be significantly enhanced after surface roughening. [5][6][7] Surface roughening using wet etching techniques is desirable due to process simplicity and low costs. However, the superior chemical stability of the GaN (0001) plane, which is the predominant plane for GaN epitaxy, prevents etching by most chemicals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Although n-type GaN has a high absorption coefficient (10 5 cm -1 ) for supra bandgap light 13 and superior minority carrier diffusion length (200-300 nm), 14 recent studies have shown that the photoactivity of n-GaN can be significantly enhanced after surface roughening. [5][6][7] Surface roughening using wet etching techniques is desirable due to process simplicity and low costs. However, the superior chemical stability of the GaN (0001) plane, which is the predominant plane for GaN epitaxy, prevents etching by most chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Direct water electrolysis using solar energy is an attractive method for hydrogen production considering energy conversion efficiency and system simplicity. Since Fujishima and Honda demonstrated direct photoelectrolysis using a TiO 2 photoanode in the 1970s, photoelectrochemical and photocatalytic properties of many semiconductors have been investigated extensively. , GaN-based semiconductors have drawn much attention for use in photoelectrolysis. Self-driven photoelectrolysis is possible using GaN for its favorable energetic alignment with the redox potentials of water . After alloying with indium, the bandgap of the semiconductor can cover the complete solar spectrum (0.7–3.4 eV) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 In our recent work, we used a simple dry-etching approach to nanoroughen a planar GaN epilayer into a nanopillar array. 24,25 The effective surface area of the n-GaN photoanode increases up to 6 times for 1.6 μm-high pillars; the plateau current density increases 84% with respect to the planar GaN. However, the dry-etching induced surface damage promotes surface recombination.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the structure applied in their work includes a p-n junction and InGaN multiple quantum wells, which complicate the PEC analysis of GaN NPs. W. J. Tseng et al [37,38] investigated the influence of length of the NPs and surface damage to NPs that occurred during the dry etching on the PEC performance of NP photoanodes, however, the photocurrents were significantly low. Nanowires grown in the bottomup approaches exhibit varying doping concentration along the nanowire length.…”
mentioning
confidence: 99%